Interpretation from the Kinetic Analysis of the Accelerated Test Results (IRAM 1674) for the Alkali-Silica Reaction - Vila González, Patricia Elizabet (2025)
The expansion of the accelerated test in mortar bars test immersed for 14 days in an aggressive solution (IRAM 1674) as well as the kinetic analysis according to RILEM AAR-2 recommendations for the study of the potencial deleterious of the aggregate in the alkali-silica reaction are presented in this work. The main objective is to contribute to the interpretation of the test results based on the analysis of the growth in expansion with the time of immersion (kinetic analysis) and in this way, get more reliability. The kinetic analysis consists in adjusting by least squares fit of the experimental data of expansion to a known mathematical model (model KAMJ), where the parameters lnk and M are obtained from. The kinetic parameters lnk and M are associated with the behavior of the reaction. Although a limit value for lnk of -6 is proposed in the literature (lower values are non-reactive aggregates and higher values are deleterious aggregate), from the analysis of the experimental data it was observed that low values of this parameter could be associated with not asymptotic growth of expansion and, therefore, the aggregates presents a deleterious behavior. The lnk/M coefficient is considered a good indicator to evaluate the behavior of the aggregate. However, in order to define a limit value for lnk/M coefficient, it is necessary to establish a correlation with the tests on long-term concrete prism (1 year or more) or the field experience of the aggregate behavior.